1984
DOI: 10.1038/ki.1984.67
|View full text |Cite
|
Sign up to set email alerts
|

H+ transport by the aldosterone-deficient rat distal nephron

Abstract: The effect of aldosterone on distal nephron acidification was investigated by comparing isolated perfused kidneys from adrenalectomized rats treated for 3 to 5 days with dexamethasone alone (10 micrograms/day i.p.) and from rats given in addition a physiologic dose of d-aldosterone (10 micrograms/day in oil s.c.). The maximal pH gradient between urine and perfusate, determined at a perfusate pH of 6.7 with glucose as the sole substrate, did not differ significantly between the aldosterone deplete and replete g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…9,26,33 Consistent with these functional classifications, application of amiloride to patients and experimental animals reduces urinary proton secretion. 9,32,34 LiCl has been used as another tool to induce the voltage-dependent defect; however, several studies have indicated that the defects induced by LiCl and amiloride are different. 35 The defect induced by administration of LiCl can be restored by Na 2 SO 4 infusion 32 and is associated with altered expression levels of H þ /K þ -ATPases and H þ -ATPases.…”
Section: Discussionmentioning
confidence: 99%
“…9,26,33 Consistent with these functional classifications, application of amiloride to patients and experimental animals reduces urinary proton secretion. 9,32,34 LiCl has been used as another tool to induce the voltage-dependent defect; however, several studies have indicated that the defects induced by LiCl and amiloride are different. 35 The defect induced by administration of LiCl can be restored by Na 2 SO 4 infusion 32 and is associated with altered expression levels of H þ /K þ -ATPases and H þ -ATPases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, aldosterone increases the activity of vacuolar H ϩ -ATPases in rat and rabbit cortical and medullary collecting ducts, and these effects are mimicked in isolated turtle bladder (32). Evidence that this mineralocorticoid is necessary for appropriate urinary acidification is also derived from patients with inborn or acquired aldosterone deficiency syndromes (distal renal tubular acidosis type IV) or in animal models with adrenalectomy or pharmacological blockade of the aldosterone pathway (10,(33)(34)(35)(36). In general, it is accepted that sustained effects of mineralocorticoids on acid secretion involve genomic mechanisms.…”
Section: Discussionmentioning
confidence: 99%